2013
DOI: 10.1007/s12687-013-0143-3
|View full text |Cite
|
Sign up to set email alerts
|

Gene–environment interactions and health inequalities: views of underserved communities

Abstract: This article examines the beliefs and experiences of individuals living in underserved ethnically diverse communities in Cleveland, Ohio, regarding the influence of genetic, social, and environmental factors on health and health inequalities. Using a community-engaged methodological approach, 13 focus groups were conducted with African American, Hispanic, and White individuals residing in the Cleveland area to explore attitudes and beliefs about genetics, genetic research, and health disparities and inequaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 38 publications
(39 reference statements)
0
12
0
Order By: Relevance
“…In the 10 years since the Human Genome Project was completed, rapid changes in genetic technology have resulted in substantial changes in the care of patients with these and other chronic diseases, which disproportionally affected racial and ethnic minority groups (Goldenberg et al, 2013; Wallace et al, 2011). This rapid infusion of genetic-genomic knowledge and changes in clinical practice present both a burden and opportunity for multi-ethnic minority nurses.…”
Section: Discussionmentioning
confidence: 99%
“…In the 10 years since the Human Genome Project was completed, rapid changes in genetic technology have resulted in substantial changes in the care of patients with these and other chronic diseases, which disproportionally affected racial and ethnic minority groups (Goldenberg et al, 2013; Wallace et al, 2011). This rapid infusion of genetic-genomic knowledge and changes in clinical practice present both a burden and opportunity for multi-ethnic minority nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative work has demonstrated that members of underserved communities may not be particularly interested in the added value of personalized genetic information relative to more significant social and environmental factors contributing to health inequities. 15 Although we were unable to access differences among underserved racial/ethnic minority patients, pharmacogenomics hold the promise to reduce health disparities through actionable observations of variable drug responses across ethnic groups for certain conditions. 16 However, these advances concomitantly hold the risk to widen disparities through reification of race as a genetic, rather than social construct, with implications for exacerbated discrimination.…”
mentioning
confidence: 99%
“…Pharmacogenetics introduces a new aspect of health education when disseminating pharmacogenetics research results to the community and when implementing pharmacogenetics tools in health care delivery. In the Forum, attendees were curious about pharmacogenetics but wanted the explanation to be relatable, a finding similar to others (Goldenberg et al, 2013;. Educating AN/AI community leaders and tribal health care administration on genetics prior to study initiation has been described; however, community-wide education on genetics in relation to dissemination was not discussed .…”
Section: Discussionmentioning
confidence: 81%